Sosialisasi Penerapan QRIS untuk Kemudahan Transaksi pada UMKM di Kotamobagu : Pengabdian - Wisnu Nugroho , Chandra; Hairil Akbar; Husna Saleh (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Digital transformation in the financial sector encourages MSMEs to adopt cashless payment systems that are more practical, secure, and efficient. The Quick Response Code Indonesian Standard (QRIS) is a digital payment solution that combines various payment methods into a single QR code. This community service activity was carried out in Kotamobagu City with the aim of providing information about the implementation of QRIS to MSME players so that they can understand, access, and use it in daily transactions. The methods used included lectures, discussions, and hands-on practice using QRIS accompanied by intensive guidance so that participants could truly master the technical steps. The results of the activity showed that participants understood the benefits of QRIS in simplifying transactions, increasing financial transparency, and expanding business reach through more modern digital services. With this outreach, it is hoped that MSMEs in Kotamobagu can adapt more quickly to developments in digital financial technology while increasing their competitiveness in the technology-based economy era.